Benefits and limitations of low-kV macromolecular imaging of frozen-hydrated biological samples - Majorovits, Endre; Schröder, Rasmus R. (BMC psychiatry, 2016)
Object contrast is one of the most important parameters of macromolecular imaging. Low-voltage transmission electron microscopy has shown an increased atom contrast for carbon materials, indicating that amplitude contrast contributions increase at a higher rate than phase contrast and inelastic scattering. Here, we studied image contrast using ice-embedded tobacco mosaic virus particles as test samples at 20-80 keV electron energy. The particles showed the expected increase in contrast for lower energies, but at the same time the 2.3-nm-resolution measure decayed more rapidly. We found a pronounced signal loss below 60 keV, and therefore we conclude that increased inelastic scattering counteracts increased amplitude contrast. This model also implies that as long as the amplitude contrast does not increase with resolution, beam damage and multiple scattering will always win over increased contrast at the lowest energies. Therefore, we cannot expect that low-energy imaging of conventionally prepared samples would provide better data than state-of-the-art 200-300 keV imaging.
Gesehen am 12.11.2019